Towards effectiveness of sukuk murabahah at CIMB bank in Malaysia - Awalludin, Noor Rohin; Al-Aidaros, Al-Hasan (Academy of IRMBR, 2016)
Sukuk is part of the Islamic capital market products. Sukuk has grown to become among the main methods of financing investments based on Islamic principles in this era.Demand for sukuk has grown rapidly in recent years because it is between the investment opportunities that offer low risk, fixed income and based on shariah principles.The most instruments of sukuk issued in Malaysia are sukuk Ijarah, sukuk Mudharabah, sukuk Istisna, and sukuk Musharakah.As it is just published in the market, the demand on these sukuk Murabahah is less applicable compared with other sukuk.Sukuk Murabahah is a sale and purchase agreement based on shariah perspective.Even so, many people still do not understand the concept and practices of sukuk Murabahah.The lack of understanding and concern in sukuk Murabahah made them at the lowest level of practices comparing to other types of sukuk.Therefore the main objective of this paper is to find out the reasons of not using sukuk Murabahah in Malaysia.An interview, through survey method using questionnaires, is employed for data collection and it is being administrated by hand to the Manager of CIMB, Kedah state.The result of the interview showed that the main reason for not using sukuk Murabahah is because lack of promotion.